PENINGKATAN KUALITAS PRODUK ALAT PERAGA EDUKATIF (APE) MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ASING - Lumbantobing, Roswita; Ambarwati, Dwi Retno Sri; Widyastuti, Susana; Muhajirin, Muhajirin; Pranowo, Dwiyanto Djoko (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2023)
This Community Service aims to help solve the problems of Educative Teaching Aids (APE) craftsmen at Pedan Klaten, Central Java, who are experiencing turmoil, especially in terms of marketing and maintaining production capacity and quality as well as developing more varied and up to date designs. Considering the potential of these educational aids craft centers need to be developed and get a touch of assistance from various related parties, especially the government and universities, assistance for capacity building and production quality and marketing needs to be done. The method implemented is the method of training and mentoring to the artisans. Community Service Activities to improve the quality of Educational Teaching Aids (APE) products run smoothly and conducively, and are very useful in providing solutions to partner problems, related to capacity building, production efficiency and effectiveness, adding production support tools, marketing development, and developing exhibition cooperation, so as to be able to increase the quality and production capacity as well as the development of Educative Teaching Aids (APE) craftsmen through various online marketing platforms. Outputs are in the form of publications through websites and social media, IA with industry, and journal articles. It is planned that the resulting product design will be proposed for Intellectual Property Rights.